2017
DOI: 10.1002/jcb.26412
|View full text |Cite
|
Sign up to set email alerts
|

Inducing indel mutation in the SOX6 gene by zinc finger nuclease for gamma reactivation: An approach towards gene therapy of beta thalassemia

Abstract: β-thalassemia is a common autosomal recessive disorder characterized by a deficiency in the synthesis of β-chains. Evidences show that increased HbF levels improve the symptoms in patients with β-thalassemia or sickle cell anemia. In this study, ZFN technology was applied to induce a mutation in the binding domain region of SOX6 to reactivate γ-globin expression. The sequences coding for ZFP arrays were designed and sub cloned in TDH plus as a transfer vector. The ZFN expression was confirmed using Western blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 43 publications
0
22
0
1
Order By: Relevance
“…(2018), reported that disruption of Sox6 binding domain results in the reactivation of γ globin expression. This study concluded that silencing Sox6 may become therapeutic strategy for β‐thalassemia treatment (Modares Sadeghi et al., 2018; Shariati et al., 2018). Another study showed the functional importance of a number of miRNAs and their target Sox6 in hereditary persistence of fetal hemoglobin deletion type‐2 (HPFH‐2) and Sicilian‐δβ‐thalassemia diseases (Fornari et al., 2017).…”
Section: Sox6 and Cardiovascular Diseasesmentioning
confidence: 93%
See 1 more Smart Citation
“…(2018), reported that disruption of Sox6 binding domain results in the reactivation of γ globin expression. This study concluded that silencing Sox6 may become therapeutic strategy for β‐thalassemia treatment (Modares Sadeghi et al., 2018; Shariati et al., 2018). Another study showed the functional importance of a number of miRNAs and their target Sox6 in hereditary persistence of fetal hemoglobin deletion type‐2 (HPFH‐2) and Sicilian‐δβ‐thalassemia diseases (Fornari et al., 2017).…”
Section: Sox6 and Cardiovascular Diseasesmentioning
confidence: 93%
“…Systemic Sox6 knockout mice do not survive after 14 days of birth due to abnormalities in cardiac and skeletal muscles development. We and others have shown that renin promoter possesses the binding site for Sox6 (Modares Sadeghi et al., 2018), and along with other transcription modulators regulate renin expression (Martinez et al., 2018). Using a loss of function mouse model, in which Sox6 is specifically knockout in renin expressing cells, Sox6 was shown to regulate renin expression and JG recruitment in response to sodium depletion and dehydration (Figure 3; Saleem et al., 2020).…”
Section: Sox6 and Renin Regulation In The Kidneymentioning
confidence: 96%
“…Endogenous loci were amplified using forward (5′ ATATACTGTCCTCAGTTTGGG 3′) and reverse (5′ TGAAGTCCACACATACCCTC 3′) primers. The mutation detection was performed as previously described …”
Section: Methodsmentioning
confidence: 99%
“… 57 Using ZFN technology, reactivation of γ-globin is achieved by inducing indel mutation of the SOX6 binding domain, and γ-globin expression increased up to 6 fold. 58 …”
Section: Nucleic Acid Therapy For β-Thalassemiamentioning
confidence: 99%